2009
DOI: 10.1002/ejoc.200900076
|View full text |Cite
|
Sign up to set email alerts
|

Short and Efficient Synthesis of Alkyne‐Modified Amino Glycoside Building Blocks

Abstract: In the light of recent progress in RNA biology, the need for molecules that bind to RNA and thus may be suited to manipulating RNA-mediated processes is steadily increasing. We present a very short and efficient synthetic route to alkynemodified neamine and 2-deoxystreptamine derivatives on a half-gram scale. These derivatives are suitable for constructing a library of potential divalent RNA binders by cop-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 46 publications
(51 reference statements)
0
15
0
1
Order By: Relevance
“…Recently, Gumireddy et al [7] and Young et al reported the first use of small molecules as inhibitors of miRNA, specifically miR-21 and miR-122, function. [8] Independently, the group of Arenz has shown that kanamycin, [9,10] 2-deoxy-streptamine (2-DOS), and neamine [11] can block let-7 processing by binding to premiR and thus block Dicer activity. Lunse et al reported an aptamer that inhibits pri-miRNA processing by targeting the apical loop domain of pri-miRNA.…”
mentioning
confidence: 99%
“…Recently, Gumireddy et al [7] and Young et al reported the first use of small molecules as inhibitors of miRNA, specifically miR-21 and miR-122, function. [8] Independently, the group of Arenz has shown that kanamycin, [9,10] 2-deoxy-streptamine (2-DOS), and neamine [11] can block let-7 processing by binding to premiR and thus block Dicer activity. Lunse et al reported an aptamer that inhibits pri-miRNA processing by targeting the apical loop domain of pri-miRNA.…”
mentioning
confidence: 99%
“…This latter was deprotected by using TFA in CH 2 Cl 2 to lead to final desired compound 6 a in 94 % yield. To obtain neamine‐ and 2‐DOS‐containing compounds, we prepared the alkyne derivatives of neamine and 2‐DOS, which had been previously described (i.e., 7 and 8 in Scheme B), and the azido derivative of nucleobase S (i.e., 9 in Scheme B). Again, a 1,3‐dipolar cycloaddition led to the desired protected compounds 6 b′ and 6 c′ in yields of 90 and 83 %, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…By choosing DNA primers complementary to miRNAs, the production of miRNA resulting from pre-miRNAs after cleavage by Dicer is related to the induced polymerization reaction. This assay was applied to the same compounds described previously [57] confirming the IC 50 values found with the previous assay. Also, Maiti and co-workers succeeded in circumventing the possible interference of fluorescent labels on pre-miRNAs with Dicer processing by using a DNA beacon bearing the fluorophore and the quencher and complementary to the targeted miRNA sequence [62].…”
Section: Focused Screening Approachmentioning
confidence: 77%
“…Aminoglycoside kanamycin B (15b), known to be a general RNA binder showed efficacy in inhibiting Dicer cleavage. This assay was then applied to a small set of aminoglycoside mimics with the most potent compound 21 (Figure 5) leading to inhibition of Dicermediated pre-let7-RNA maturation with an IC 50 of 0.65 μM [57]. Recently, our group has screened several classes of antibiotics (aminoglycosides, tetracyclines, macrolides, lincosamides as well as linezolid, chloramphenicol and puromycin) [58], as inhibitors of Dicer processing upon binding to four pre-miRNAs precursors of oncogenic miR-372, miR-373, miR-17 and miR-21 [59].…”
Section: Focused Screening Approachmentioning
confidence: 99%
See 1 more Smart Citation